Variation in current prescription practice of stereotactic body radiotherapy for peripherally located early stage non-small cell lung cancer: Recommendations for prescribing and recording according to the ACROP guideline and ICRU report 91. (January 2020) - de Jong, Evelyn E.C.; Guckenberger, Matthias; Andratschke, Nicolaus; Dieckmann, Karin; Hoogeman, Mischa S.; Milder, Maaike; Møller, Ditte Sloth; Nyeng, Tine Bisballe; Tanadini-Lang, Stephanie; Lartigau, Eric; Lacornerie, Thomas; Senan, Suresh; et al.
Highlights: First multicentre study on lung SBRT planning using the ICRU-91 reporting standards. A large variation in prescription practice across institutions exists. Report explicitly both PTV and GTV/ITV D98%, D2% and Dmean. Dose prescription of 3 × 15 Gy should lead to a minimum PTV D98% of 100 Gy BED10Gy . The mean GTV dose should be 150 Gy BED10Gy . Abstract: Background and purpose: In 2017 the ACROP guideline on SBRT for peripherally located early stage NSCLC was published. Later that year ICRU-91 about prescribing, recording and reporting was published. The purpose of this study is to quantify the current variation in prescription practice in the institutions that contributed to the ACROP guideline and to establish the link between the ACROP and ICRU-91 recommendations. Material and methods: From each of the eight participating centres, 15 SBRT plans for stage I NSCLC were analyzed. Plans were generated following the institutional protocol, centres prescribed 3 × 13.5 Gy, 3 × 15 Gy, 3 × 17 Gy or 3 × 18 Gy. Dose parameters of the target volumes were reported as recommended by ICRU-91 and also converted to BED10Gy . Results: The intra-institutional variance in D98%, Dmean and D2% of the PTV and GTV/ITV is substantially smaller than the inter-institutional spread, indicating well protocollised planning procedures are followed. The median values per centre ranged from 56.1 Gy to 73.1 Gy (D2%), 50.4 Gy to 63.3 Gy (Dmean) and 40.5 Gy to 53.6 Gy (D98%) for the PTV and from 57.1 Gy to 73.6 Gy (D2%), 53.7 Gy to 68.7 Gy (Dmean) and 48.5 Gy to 62.3 Gy (D98%) for the GTV/ITV. Comparing the variance in PTV D98% with the variance in GTV Dmean per centre, using an F-test, shows that four centres have a larger variance in GTV Dmean, while one centre has a larger variance in PTV D98% ( p values <0.01). This shows some centres focus on achieving a constant PTV coverage while others aim at a constant GTV coverage. Conclusion: More detailed recommendations for dose planning and reporting of lung SBRT in line with ICRU-91 were formulated, including a minimum PTV D98% of 100 Gy BED10Gy and minimum GTV/ITV mean dose of 150 Gy BED10Gy and a D2% in the range of 60–70 Gy.